Application of decatastrophize (Use of SDSS and MCDA to prepare for disasters or plan for multlple hazards) Decision Support Systems (DSS) tool - Mettas, Christodoulos; Evagorou, Evagoras S.; Papadopoulos, Marinos; Konstantinou, Alexia; Panayiotou, Charalambos; Foka, Anna; Auclair, Samuel; Monfort, Daniel; Kampanis, Nikolas; Spanoudaki, Katerina; Synolakis, Costas; Kalligeris, Nikos; et al. (My University, 2018)
DECATASTROPHIZE (UsE of SDSS and MCDA To prepAre for diSasTeRs Or Plan for multlplE HaZards) was financed from the European Union's Directorate-General humanitarian aid and civil protection (DG-ECHO) under Grant Agreement ECHO/SUB/2015/713788/PREP02. This project developed tools that can be used effectively in early warning and alert systems ensuring lives and protecting people, properties and the environment from natural/man-made hazards. The aim of the project was to use/adapt existing models, systems or tools in an interactive and synergic capacity to prepare for disasters and plan for multi-hazard incidents. Through DECATASTROPHIZE, a web-based Geo-Spatial Early-warning Decision Support Systems (GE-DSS) platform was developed in combination with Geographic Information Systems (GIS), keeping systems interoperability and organizations cooperation in mind. The …
Keywords: Decatastrophize; Application; SDSS; MCDA; Disasters; Multlple hazards; Decision Support Systems (DSS)